New candidate loci identified by array‐CGH in a cohort of 100 children presenting with syndromic obesity. Issue 8 (29th April 2014) - Vuillaume, Marie‐Laure; Naudion, Sophie; Banneau, Guillaume; Diene, Gwenaelle; Cartault, Audrey; Cailley, Dorothée; Bouron, Julie; Toutain, Jérôme; Bourrouillou, Georges; Vigouroux, Adeline; Bouneau, Laurence; Nacka, Fabienne; et al.
<x xml:space="preserve">Abstract</x> Syndromic obesity is defined by the association of obesity with one or more feature(s) including developmental delay, dysmorphic traits, and/or congenital malformations. Over 25 syndromic forms of obesity have been identified. However, most cases remain of unknown etiology. The aim of this study was to identify new candidate loci associated with syndromic obesity to find new candidate genes and to better understand molecular mechanisms involved in this pathology. We performed oligonucleotide microarray‐based comparative genomic hybridization in a cohort of 100 children presenting with syndromic obesity of unknown etiology, after exhaustive clinical, biological, and molecular studies. Chromosomal copy number variations were detected in 42% of the children in our cohort, with 23% of patients with potentially pathogenic copy number variants. Our results support that chromosomal rearrangements are frequently associated with syndromic obesity with a variety of contributory genes having relevance to either obesity or developmental delay. A list of inherited or apparently de novo duplications and deletions including their enclosed genes and not previously linked to syndromic obesity was established. Proteins encoded by several of these genes are involved in lipid metabolism (ACOXL, MSMO1, MVD, and PDZK1) linked with nervous system function (BDH1 and LINGO2), neutral lipid storage (PLIN2), energy homeostasis and metabolic processes (CDH13, CNTNAP2, CPPED1, NDUFA4, PTGS2, and SOCS6). © 2014 Wiley Periodicals, Inc.